Enseñanza de estrategias metacognitivas para el fortalecimiento de la comprensión lectora (2020)
Reading comprehension is one of the challenges our boys and girls face at the beginning of school age, this activity becomes complex when there is ignorance in the use of metacognitive strategies that help the schoolchild to understand texts, to give them meaning so that the student can achieve self-regulated learning. Due to the above, teachers must know and implement strategies that help the student, to strengthen their understanding process, which will allow them to understand and use the didactics learned, not only in the area of language, but also in the rest of the subjects during the school calendar, and especially, reach a metacognitive level that helps them self-manage their learning. It is for this reason that the purpose of the research is to analyze and characterize the didactic elements that intervene in the teaching of metacognitive strategies, so that, in this way, the teacher can strengthen their classroom practices in relation to the use of strategies metacognitive. To fulfill the purpose of the research work, a non-experimental approach will be developed, without deliberately manipulating the categories, that is, it is an investigation where independent categories cannot be intentionally varied to see their effect on other categories , the result of the proposed purposes allow obtaining pedagogical orientations for the use of metacognitive strategies in the strengthening of reading comprehension.